2018
DOI: 10.1103/physrevb.97.064107
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and properties of selenium trihydride at high pressures

Abstract: The chemical reaction products of molecular hydrogen (H 2 ) with selenium (Se) are studied by synchrotron x-ray diffraction (XRD) and Raman spectroscopy at high pressures. We find that a common H 2 Se is synthesized at 0.3 GPa using laser heating.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(38 citation statements)
references
References 44 publications
1
37
0
Order By: Relevance
“…Moreover, a host-guest I4/mcm-(H 2 Se) 2 H 2 structure, which was analogous to the one observed in (H 2 S) 2 H 2 , formed above 4.2 GPa. Both of these hydrides of selenium decomposed above 24 GPa at 300 K. 392 In addition to H 2 Se, a recent study synthesized a Cccm-H 3 Se phase at 4.6 GPa and 300 K. At 170 K Cmcm-H 3 Se was found to persist up to 39.5 GPa. Raman measurements and visual observations suggested that metalization occurred above 23 GPa.…”
Section: Seleniummentioning
confidence: 99%
“…Moreover, a host-guest I4/mcm-(H 2 Se) 2 H 2 structure, which was analogous to the one observed in (H 2 S) 2 H 2 , formed above 4.2 GPa. Both of these hydrides of selenium decomposed above 24 GPa at 300 K. 392 In addition to H 2 Se, a recent study synthesized a Cccm-H 3 Se phase at 4.6 GPa and 300 K. At 170 K Cmcm-H 3 Se was found to persist up to 39.5 GPa. Raman measurements and visual observations suggested that metalization occurred above 23 GPa.…”
Section: Seleniummentioning
confidence: 99%
“…Two peaks at 257 (A 1g(MoSe) ) and 287 cm −1 (E 2g(MoSe) ) are observed. [ 31 ] In addition, a new peak at 2365 cm −1 with increased peak intensity appears as the voltage varied from 0.05 to −0.15 V. Similar to the SH vibration band in the case of MoS 2 , this Raman peak is consistent with SeH stretching vibrations, [ 32,33 ] indicating that the H atoms are adsorbed to the active Se atoms to form intermediate MoSe 2 ‐H species here. The deduction is also verified by DFT simulation about the hydrogen adsorption of MoSe 2 (Figure S5, Supporting Information).…”
Section: Resultsmentioning
confidence: 69%
“…According to Pace et al 1 , Zhang et al 2 claim that they synthesized a new compound H 3 Se which is different from the theoretically predicted one 3 that was also synthesized under similar conditions by Pace et al 4 . The material synthesized by Zhang et al 2 is clearly the same as theoretically predicted 3 and subsequently synthesized by Pace et al 4 ; this can be seen based on the presented x-ray diffraction (XRD) and Raman data.…”
Section: Main Textmentioning
confidence: 83%
“…According to Pace et al 1 , Zhang et al 2 claim that they synthesized a new compound H 3 Se which is different from the theoretically predicted one 3 that was also synthesized under similar conditions by Pace et al 4 . The material synthesized by Zhang et al 2 is clearly the same as theoretically predicted 3 and subsequently synthesized by Pace et al 4 ; this can be seen based on the presented x-ray diffraction (XRD) and Raman data. While we admit that Zhang et al 2 use the nomenclature H 3 Se for the molecular (H 2 Se) 2 H 2 at low pressure 4 , we stress that this was made on purpose to emphasize the connection to the expected high-pressure behavior that is analogous with the behavior of H 3 S 5-8 .…”
Section: Main Textmentioning
confidence: 83%
See 1 more Smart Citation